Tomorrow Began Yesterday - Lidin, Konstantin (project baikal, 2014)
The phenomenon of the sixtiers was prepared by the previous historical period. The period after the World War II comprises a fundamental change of the world order – from a multipolar world to a confrontation of two superpowers and two ideological systems, and, at the same time, formation of a complex of international organizations on a global scale. In this context, the Soviet architecture made a sharp turn from Stalin’s Empire style to an extreme ascetism – the continuation of constructivism of the early XXth century. The Irkutsk architectural school, unlike the main flow of the 1960s, developed the style of Neo-Brutalism. The article draws parallels between Neo-Brutalism of the Irkutsk school and “a severe style” of the Soviet pictorial art of the same period.